Netrin-1 regulates the inflammatory response of neutrophils and macrophages, and suppresses ischemic acute kidney injury by inhibiting COX-2 mediated PGE2 production - Ranganathan, Punithavathi Vilapakkam (2013)
Netrin-1 regulates inflammation but the mechanism by which this occurs is unknown. Here we explore the role of netrin-1 in regulating the production of the prostanoid metabolite PGE2 from neutrophils in in vitro and in vivo disease models. Ischemia reperfusion in wild-type and RAG-1 knockout mice induced severe kidney injury that was associated with a large increase in neutrophil infiltration and COX-2 expression in the infiltrating leukocytes. Administration of netrin-1 suppressed COX-2 expression, PGE2 and thromboxane production, and neutrophil infiltration into the kidney. This was associated with reduced apoptosis, inflammatory cytokine and chemokine expression, and improved kidney function. Treatment with the PGE2 receptor EP4 agonist enhanced neutrophil infiltration and renal injury which was not inhibited by netrin-1. Consistent with in vivo data, both LPS and IFNγ-induced inflammatory cytokine production in macrophages and IL-17-induced IFNγ production in neutrophils were suppressed by netrin-1 in vitro by suppression of COX-2 expression. Moreover, netrin-1 regulates COX-2 expression at the transcriptional level through the regulation of NFκB activation. Thus, netrin-1 regulates the inflammatory response of neutrophils and macrophages through suppression of COX-2 mediated PGE2 production. This could be a potential drug for treating many inflammatory immune disorders.